Urban Commoning Under Adverse Conditions: Lessons From a Failed Transdisciplinary Project - Zielke, Julia; Hepburn, Paul; Thompson, Matthew; Southern, Alan (Frontiers in Sustainable Cities, 2021)
While the commons and commoning are generally associated with community-based ecosystems at the localised scale of the neighbourhood, ambitious reinterpretations explore possibilities for scaling up commoning as a collaborative and sustainable form of urban governance engaging multiple stakeholders through the quintuple helix. Inspired by the City as Commons approach first imagined and formulated in Bologna, Italy, this paper presents original findings from a transdisciplinary action research project for studying and cultivating commoning-as-governance in a politically disaffected and economically marginalised inner-city neighbourhood in Liverpool, England. It examines the social relations (re)constituting an urban ecosystem for commoning and asks how such initiatives for designing collaborative programmes for transforming urban environments through public-civic partnerships might work in contexts in which the material and affective resources for commoning have been exhausted by post-democratic privatisation and neoliberal austerity. Drawing on theories of radical democracy and post-politics, the City as Commons approach is critically evaluated and argued to be insufficient to the challenging task of engendering commoning in the disintegrating urban neighbourhoods that would arguably benefit most from such activities. The paper tells the story of how this transdisciplinary project ultimately failed in its aims and, through engagement with recent interventions on the politics of failure in the neoliberal university, reflects on the implications for future action research on commoning.